THREE-STAGE FURNACE FOR BIOMASS THERMAL TREATMENT - Jan Mikula; Dusan Nascak; Jan Kerekanic (European Scientific Journal, ESJ, 2014)
Currently, use of biomass energy potential accounts for less than 20 %, mainly because of the high energy costs. The reasons why the energy costs are high are that the energy transformation efficiency is low and the logistics costs are high. A systematic increase in the thermal processes for energy recovery from biomass has a great prospect. The conversion of biomass into energy is carried out by combustion or gas production through pyrolysis and gasification. In terms of energy and thermodynamic efficiency, the combined method consisting in the production of gas is most suitable. The combined method consists of pyrolysis, the primary combustion, gasification and secondary combustion. The optimal solution is achieved at the maximum calorific value of produced gas. The research of the proposed process was carried out by methods of physical and mathematical modelling. An economic efficiency of biomass energy use depends on the costs of biomass and its modification and it also depends on its thermal recovery efficiency. This paper compares three basic methods of heat generation from biomass: single-stage, two-stage and three-stage. The three-stage furnace designed and created by the results of modelling and experimental verification is presented. In the furnace is carried out high-temperature pyrolysis and generated separately pyrolysis and synthesis gas.